The Challenge of Targeting Notch in Hematologic Malignancies - Hernandez Tejada, Fiorela N.; Galvez Silva, Jorge R.; Zweidler-McKay, Patrick A. (Frontiers in Pediatrics, 2014)
Notch signaling can play oncogenic and tumor suppressor roles depending on cell type. Hematologic malignancies encompass a wide range of transformed cells, and consequently the roles of Notch are diverse in these diseases. For example Notch is a potent T cell oncogene, with >50% of T cell acute lymphoblastic leukemia (T-ALL) cases carry activating mutations in the Notch1 receptor. Targeting Notch signaling in T-ALL with gamma secretase inhibitors, which prevent Notch receptor activation, has shown pre-clinical activity, and is under evaluation clinically. In contrast, Notch signaling inhibits acute myeloblastic leukemia growth and survival, and although targeting Notch signaling in AML with Notch activators appears to have pre-clinical activity, no Notch agonists are clinically available at this time. As such, despite accumulating evidence about the biology of Notch signaling in different hematologic cancers, which provide compelling clinical promise, we are only beginning to target this pathway clinically, either on or off. In this review we will summarize the evidence for oncogenic and tumor suppressor roles of Notch in a wide range of leukemias and lymphomas, and describe therapeutic opportunities for now and the future.